The armoured Trains of the Russian empire of times of the first world war - H. V. Korobov (History of science and technology, 2015)
The article is devoted to the history of the armoured trains’ creation and functioning of the World War I in Russian Empire. The features of their design, development, testing and putting into operation was indicated. The structure, composition and operation of the armoured trains in  railway transport of Russian Empire was covered.